Towards a more sustainable surface transport infrastructure: a case study of applying multi criteria analysis techniques to assess the sustainability of transport noise reducing devices. (20th January 2016) - Oltean-Dumbrava, Crina; Watts, Greg; Miah, Abdul
Abstract: The surface transport infrastructure (i.e. road and rail) has seen increasing pressure in recent years to achieve better sustainability performance. Transport Noise Reducing Devices (NRDs) form a major part of the surface transport infrastructure system in mitigating undesirable surface noise pollution to impacted communities. Their sustainability is a growing interest for practitioners and policy makers in this area as NRDs projects now have to balance integrating and assessing social, environmental, and economic objectives besides meeting key technical requirements. This paper presents an account of the first study carried out to assess the absolute sustainability of NRDs via the application of multi criteria analysis (MCA) techniques. The general procedure, selection of criteria, data gathering, and the use of three MCA techniques, SAW (Simple Additive Weighting), PROMETHEE (Preference Ranking Organisation MeTHod for Enrichment Evaluations), and ELECTRE III (Elimination et Choice Translating Reality), to assess the absolute sustainability of two built and operating European NRDs projects (one in Spain, and one in Italy) is presented. The novel concept of defining an Optimal Hypothetic Ideal Solution (OHIS) to assess the sustainability of NRDs in absolute terms to achieve this end is also introduced and discussed. The presented case studies will thus provide a useful model for practitioners to adopt or amend to conduct their own assessments of NRDs' sustainability. The paper further concludes that the generation of index values by the three MCA techniques to denote the overall absolute sustainability of solutions is a useful feature for communicating the sustainability of NRDs across a broad range of stakeholders, and for conducting "what-if" analyses. The presented research could also support broader aims of developing harmonized sustainability standards for the NRDs industry to adopt and so forward the sustainability transport agenda.